2011
DOI: 10.5021/ad.2011.23.s3.s310
|View full text |Cite
|
Sign up to set email alerts
|

The Neumann Type of Pemphigus Vegetans Treated with Combination of Dapsone and Steroid

Abstract: Pemphigus vegetans is a rare variant of pemphigus vulgaris and is characterized by vegetating lesions in the inguinal folds and mouth and by the presence of autoantibodies against desmoglein 3. Two clinical subtypes of pemphigus vegetans exist, which are initially characterized by flaccid bullae and erosions (the Neumann subtype) or pustules (the Hallopeau subtype). Both subtypes subsequently develop into hyperpigmented vegetative plaques with pustules and hypertrophic granulation tissue at the periphery of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Research has shown that agents such as azathioprine, mycophenolate mofetil and dapsone may improve the rate of remission in these patients 1 4. Recently, rituximab therapy was shown to be useful in treating recalcitrant PVeg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that agents such as azathioprine, mycophenolate mofetil and dapsone may improve the rate of remission in these patients 1 4. Recently, rituximab therapy was shown to be useful in treating recalcitrant PVeg.…”
Section: Discussionmentioning
confidence: 99%
“…Pemphigus vegetans (PVeg) is the rarest clinical variant of PV, accounting for 1–2% of all pemphigus. It is characterised by vegetating plaques primarily localised to the flexural areas 1. Its management is similar to that of PV.…”
Section: Introductionmentioning
confidence: 99%
“…Pyodermatitispyostomatitis vegetans can clinically and histopathologically resemble pemphigus vegetans and only indirect and direct immunofluorescence studies can accurately distinguish between these two entities. 6 …”
Section: Cobblestone Mouth: An Exuberant Oral Presentation Of Pemphigmentioning
confidence: 97%
“…6 Pyodermatitispyostomatitis vegetans can clinically and histopathologically resemble pemphigus vegetans and only indirect and direct immunofluorescence studies can accurately distinguish between these two entities.…”
Section: Una Boca En Empedrado: Una Presentación Oral Exuberante De Pmentioning
confidence: 99%